The problem of compliance of the framework conditions of the policy of economic order with the basic social values - Gvelesiani, Revaz (Ivane Javakhishvili Tbilisi State University Press, 2019)
An essential component of economic policy problems is the divorce between reality and the desired socio-economic situation. In order to overcome this problem, the necessary condition is to comply with the basic public values (freedom, justice, security, progress) of the economic policy objectives and the decisions taken to implement them. This is what determines both the rationality of economic policy decisions and the effectiveness of their implementation in practice. The economic order and legal-legislative system must always be focused on the core public values and goals. This is why economic order policy strives to achieve consistency between the public value system and the formation of framework conditions of economic order. This makes it clear that order politics is of instrumental nature in achieving sociopolitical goals and it is fundamentally different in different socio-economic systems (Gvelesiani, Gogorishvili, 2018, 11). The more the ability to self-regulate market coordination is expected during the formation of framework conditions of economic order, the less the risk of random interventions. Priority is given to consistent, long-term and cautious economic policies. Particular caution should be exercised when trying to establish the framework conditions of economic order with the aim of improving self-regulation of market coordination.
 Boulding, K.E. (1958), Principles of Economic Policy, 4th printing, Englewood Cliff s, 1964, p.117.  Giersch H. (1961), Allgemeine Wirtschaftspolitik (Erster Band: Grundlagen), unveraenderter Nachdr., Wiesbaden, 1990, S.83. (in German)  Gvelesiani R. (2016), Individuals and Economic Groups Interests and Behaviour in the Economic and Political Decision-making Process, European Journal of Business Research (EJBR), IABE, Volume 16, №1,. ISSN: 1945-2977, University of Pisa, Italy, Editor: Johannes Kepler University Linz, Austria, p. 97-103.  Gvelesiani R. (2017), The Problem of Considering Possible Consequences of the Consistent Reforms in the Economic-Political Decisions. Review of Business research (RBR), Volume 17, №2, ISSN: 1546-2609, University of Sassari, Italy, Editor: University of Osijek, Croatia, p.19-24.  Gvelesiani R. (2017), Possibilities of Implementing the Practical Economical Politics Rationally. European Journal of Business Research (EJBR), Volume 17, №2, ISSN: 1945- 2977, dx.doi.org/10.18374/EJBR-17-2.3, New York Institute of Technology, USA, editor-inchief: Professor Christine Duller, Johannes Kepler University Linz, Austria, p.25-30.  Gvelesiani R., Gogorishvili I. (2018), gadawyvetilebis mirebis teqnologia ekonomikur politikashi. Tbilisi, gv. 11-12; 43-44. [Decision Making Technology in Economic Policy, Tbilisi, pp. 11-12; 43-44; 52. (in Georgian).  Gvelesiani R. (2017), ziritad sazogadoebriv faseulobata shoris arsebuli cinaagmdegobebi da mati dazlevis problema. “ekonomika da biznesi” X, №1, gv. 14-24. [The Contradictions between Core Social Values and the Problem of Overcoming Them, Economics and Business, Volume X, No. 1, Tbilisi, pp. 14-24.] (in Georgian).  Gvelesiani R. (2018). socialuri sabazro ekonomikis koncefciis damokidebuleba ziritad sazogadoebriv girebulebebtan. “ekonomisti”, №3, tomi XIV, ISSN: 1987-6890, gv.26-34. [The Relationship between the Concept of the Social Market Economy and the Basic Social Values] Economist, No. 3, Volume XIV, ISSN: 1987-6890, Tbilisi, pp.26-34. (in Georgian).  Gvelesiani R. (2016). ekonomikuri cesrigis specifi kuri charcho-pirobebis formirebis problema, I saertashoriso samecniero konferenciis “globalizaciis gamocvevebi ekonomikasa da biznesshi” masalebi; gamomcemloba “univesali,” Tbilisi, gv. 163-166. [The Problem of Forming Specifi c Framework Conditions of Economic Order. Proceedings of the 1st International Scientifi c Conference “Globalization Challenges in Economics and Business”, “Universali,” Tbilisi, pp.163–166. (in Georgian).  Hamilton, A., J. Madison und J. Jay (1787-1788), The Federalist Papers, hrsg. v. C. Rossiter, New York 1961, p.472.  Hayek F.A. (1979), Law, Legislation and Liberty, Volume III – The Political Order of a Free People, Chicago, London, Wiederabdruck in: Vanberg, V. (Hrsg.), Hayek Gesammelte Schriften Bd. B4, Recht, Gesetzgebung und Freiheit, Tuebingen 2003, S.128.  Hayek F.A. (2003), Rechtsordnung und Handelnsordnung, in: Streit, M. E. (Hrsg.), Hayek Gesammelte Schriften Bd. A4, Rechtsordnung und Handelnsordnung, Tuebingen, S. 217. (in German)  Kant I. (1781, 1788, 1790), Die drei Kriterien in ihrem Zusammenhang mit dem Gesamtwerk, Jubilaeumsausgabe anlaessl. Des 125-jaehrigen Bestehens d. philosophischen Bibliothek, Hmaburg, 1993, S. 390. (in German).  Mill J.S. (1859), On Liberty; in ders.: Utilitarism, Liberty, Representative Government, neuausgabe, hrsg. v. H. B. Acton, London 1972, p. 75.  Sartori G. (1987), The Theory of Democracy Revisited, 2 Bde., Chatham, N. J., Sonderausgabe Darmstadt 1997, S. 337.  Streit M. E. (2005), Theorie der Wirtschaftspolitik, 6. Aufl age, Stuttgart, S.26-30; 49-53; 257; 262. (in German).  Tuchtfeldt E. (1971a), Moral Suasion in der Wirtschaftspolitik; in E. Hoppmann(Hrsg.): Konzertierte Aktion – Kritische Beitraege zu einem Experiment, Frankfurt am Main, S. 32. (in German).
Keywords: key public values, economic order policy, framework conditions of economic order, economic interests, conflicts of interest